Political networking strategy and firm performance: a moderated mediation model. Issue 4 (10th October 2016) - Lin, Yaqing; Li, Yan; Zhao, Shuming; Armstrong, Steven
Abstract : Purpose: By incorporating the resource-based view with the dynamic capability view, this study aims to examine the link between corporate political networking strategy and firm performance in transition economies by focusing on the mediating role of corporate entrepreneurship and the moderating role of dysfunctional competition. Design/methodology/approach: A large-scale questionnaire survey was conducted among 1, 300 senior managers from 650 enterprises in China, and valid survey data were obtained from 401 enterprises. Findings: Empirical results demonstrate that political networking strategy is positively related to firm performance and that this relationship is fully mediated by corporate entrepreneurship. Moderated path analysis indicates that dysfunctional competition strengthens the direct effect of political networking strategy on corporate entrepreneurship and its indirect effect on firm performance via corporate entrepreneurship. Originality/value: This research is among the first to examine the mediating mechanism underlying the relationship between political networking strategy and firm performance in the context of transition economies. In addition, existing research has seldom discussed the effects on corporate entrepreneurship of external resource acquisition from government sources. This research fills this important gap and identifies the condition under which political networking benefits corporate entrepreneurship.